2010
DOI: 10.1086/652903
|View full text |Cite
|
Sign up to set email alerts
|

Press Coverage and Political Accountability

Abstract: In this paper we estimate the impact of press coverage on citizen knowledge, politicians' actions, and policy. We find that a poor fit between newspaper markets and political districts reduces press coverage of politics. We use variation in this fit due to redistricting to identify the effects of reduced coverage. Exploring the links in the causal chain of media effects --voter information, politicians' actions and policy --we find statistically significant and substantively important effects. Voters living in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

23
333
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 614 publications
(369 citation statements)
references
References 31 publications
23
333
0
1
Order By: Relevance
“…They are more likely to practice defensive medicine when the likelihood of negative publicity increases. Our results complement recent findings within the field of political economy [1][2][3][4]. These studies indicate that elected representatives are responsive to the needs and the preferences of their constituency when they are closely monitored by the media.…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…They are more likely to practice defensive medicine when the likelihood of negative publicity increases. Our results complement recent findings within the field of political economy [1][2][3][4]. These studies indicate that elected representatives are responsive to the needs and the preferences of their constituency when they are closely monitored by the media.…”
Section: Discussionsupporting
confidence: 87%
“…Snyder and Strömberg found that counties in the USA that were well covered by newspapers during the period 1991-2002 received more federal funding [2]. Similar results have been reported from other countries.…”
Section: Introductionsupporting
confidence: 71%
See 1 more Smart Citation
“…Another example is Snyder and Strömberg (2010) investigating how different levels of political competition induced by press coverage affect in versus against party line voting by members of the US Congress. 8 Becker et al (2009) analyze the effect of political competition on politicians' outside earnings, i.e.…”
Section: Related Literaturementioning
confidence: 99%
“…By estimating the impact of news coverage of lifts of immunity on the likelihood of resignation, we show that the media can help holding representatives accountable prior to the regular end of their mandate or function. Because we investigate the behavior of representatives, our study also relates to the literature on the effects of media on policy making (Besley and Burgess, 2002;Strömberg, 2004b;Eisensee and Strömberg, 2007;Snyder and Strömberg, 2010) and political elites (Campante and Hojman, 2013;Clinton and Enamorado, 2014;Arceneaux et al, 2015;Garcia-Jimeno and Yildirim, 2015).…”
Section: Introductionmentioning
confidence: 99%